Pelatihan Pemanfaatan Aplikasi Excel Sebagai Peningkatan Kemampuan Komputer Dasar Dalam Mengolah Data - Simalango, Holong Marisi (Community : Jurnal Pengabdian Pada Masyarakat, 2024)
Devotion to society in the form of Training to Maitreyewira High School students, especially the 2022 Force Language and Cultural Sciences (XI IBB) classes. Training with Excel application use. This devotion aims to improve competence in basic and reliable computers and master Excel Applications in processing data and preparing Excel-related activities for both tasks or work in the field. Training participants are as many as twenty people. Training is conducted offline in the computer laboratory room and ends with an evaluation of material mastery. The results of this activity showed that overall, each indicator of the participants’ questionnaire showed that the material and the patient were in good categories and excellent.